Photoelastic analysis of thermal stresses - Burger, Christian Peter (Department of Mechanical Engineering, 2015)
Developments in the application of photoelastic techniques to the study of thermal stress problems are here briefly reviewed, then followed by a short introduction to the relevant photoelastic and thermoelastic theories. A new method for the study of transient thermal stresses; as well as stresses due to the internal heating of nuclear reactor parts, is described. In this method hot or cold liquid is circulated continuously over the surfaces of a composite photoelastic model which incorporates the sandwich type of built in polariscope developed by Tramposch and Gerard. By varying the temperatures· of the liquid and the flow rates to one or all the surfaces of a model, the temperature profile in the model can be controlled at will. The instantaneous temperature profile is sensed by banks of thermocouples which are scanned in sequence with a specially built rotary switch, and their outputs are recorded on a storage oscilloscope. The thermocouples here, are for the first time, mounted outside the sandwiched polariscope in a separate sensor block where they do not disturb the photoelastic fringe pattern of the thermally induced stresses. The stress fringe patterns are observed continuously and photographed according to a set time schedule in synchronism with the temperature pattern on the oscilloscope screen. Thus a simultaneous record of the thermal stresses as they develop in the model 1 and the temperature profiles that cause them, is obtained. The test method is applied to the study of thermal stresses in an unconstrained thick plate with a temperature gradient across its thickness. Two models are used, one of uniform thickness and another which has a small change in thickness at a Single radiused shoulder. The ratio of thick to thin section is 1.1 to 1. Three basic types of temperature gradient are induced in each model, i.e. firstly: equal heating on both faces of a plate initially at uniform temperature; secondly: heating on one side only, of a plate initially at uniform temperature; and thirdly: heating on the cold side only, of a plate with an initial linear temperature gradient between a cold side and a hot side.